Music and imagination - Copland, Aaron, 1900-1990 (Charles Eliot Norton lectures, 1952)
The six talks were intended as a free improvisation on the general theme of the role imagination plays in the art of music. The first half of the book treats of the musical mind at work in its different capacities as listener, interpreter, or creator. The second half discusses more specifically recent manifestations of the imaginative mind in the music of Europe and the Americas. The lectures were followed in each instance by short concerts.--Preface.